GAMBARAN PROSES PEMULIHAN PENDERITA GANGGUAN MENTAL - Dhaniswara Widyaningsih, Bernadeta (Widya Warta, 2013)
Recovery from the mental disorder needs viewing psychologicallytoassessemotional problems, especially problemsof familysupport.The source ofmentaldisorderis mostly the effect of dynamicinteractionbetween an individual and his environment. The results ofthe study on thepatients whoalready got recovered showthat self-concept toward their own problem before recovery, family support(especially from thosewhofaithfully accompaniedand understood the patients), occupation, and peoplewho want toacceptthe subject involved insocial activitycan help the process of recovery of the patients.